96 DYAMIC CONTRAST-ENHANCED MAGNETIC RESONANCE IMAGING PHARMACODYNAMIC STUDY OF SORAFENIB IN METASTATIC RENAL CELL CARCINOMA: PRELIMINARY RESULTS OF A RANDOMIZED, PHASE II TRIAL. (1st March 2007) - Yang, C.; Hahn, O.; Medved, M.; Karczmar, G.; Kistner, E.; Karrison, T.; Manchen, B.; Mitchell, M.; Ratain, M.; Stadler, W. M.
Abstract : Background: Sorafenib is an oral antiangiogenic agent with activity in renal cell cancer (RCC). We conducted a randomized, placebo-controlled trial to investigate if dynamic contrast-enhanced MRI (DCE-MRI) is a pharmacodynamic (PD) marker for sorafenib. Method: Patients were randomized in a double-blind manner to placebo, 200 mg bid sorafenib, or 400 mg bid sorafenib. DCE-MRI was performed at baseline and after 28 days of therapy, at which time placebo patients were rerandomized to low- or standard-dose sorafenib. RECIST-based progression was determined by CT scans performed every 12 weeks. DCE-MRI parameters, including the area under the contrast concentration versus time curve for 90 seconds after contrast injection (IAUC90), were calculated for a tumor region of interest in a blinded manner. Plasma steady-state sorafenib concentrations were obtained on day 28. Results: To date, 43 of a planned 66 patients have been enrolled, and 34 have undergone two protocol-defined MRIs, of which 33 are technically evaluable for the study end points. All analyses were conducted using the log ratio of the mean IAUC90 at 4 weeks versus the mean at baseline. The estimates of the log ratio and the corresponding standard deviations in the placebo, 200 mg, and 400 mg cohorts were 0.032 (± 0.235), −0.066 (± 0.138), and −0.281 (± 0.430), respectively ( p = .0156 for linear trend between dose and the log ratio of IAUC90). These correspond to relative changes of +3%, −6%, and −24% in the placebo, 200 mg, and 400 mg cohorts, respectively. In the 27 patients with available plasma sorafenib levels, change in IAUC90 did not correlate with sorafenib steady-state levels ( p = .7507). Current median follow-up is 20 weeks. Using a Cox proportional hazards model, IAUC90 change is not a significant predictor of progression-free survival ( p = .229). The mean arterial pressure increased with sorafenib dose, but no correlation with IAUC90 change was detected ( p = .445). Conclusions: DCE-MRI is a PD marker for sorafenib, and intrapatient variability is similar to previous reports, but the magnitude of effect in this prospective blinded study is less than previously reported. Ongoing analyses seek to assess the value of other DCE-MRI markers, such as Ktrans, and to correlate the DCE-MRI markers with more mature clinical follow-up data.